2020
DOI: 10.9755/ejfa.2020.v32.i1.2051
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional potential of grape by-products from the area of Slovakia and Austria

Abstract: Current experiments with farm animals showed that it is possible to use grape by-products as a source of nutrients in animal nutrition. In the present experiment, we hypothesize that one reason for the variation among feeding trials, besides production steps affecting byproduct quality in winery, the variation among cultivars may have substantial contribution. The main aim of this study was to analyse grape pomace and stems from the area of Slovak Republic and Austria to evaluate their nutritional value for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…This difference depends on both grape cultivar and type of winemaking by-products. While for grape pomace, the red cultivars present superior values of proteins than the white grapes pomace, for stems higher significant values of proteins than the red grapes have been found (Hanušovský et al, 2020).…”
Section: Proteins Peptides and Amino Acidsmentioning
confidence: 81%
See 3 more Smart Citations
“…This difference depends on both grape cultivar and type of winemaking by-products. While for grape pomace, the red cultivars present superior values of proteins than the white grapes pomace, for stems higher significant values of proteins than the red grapes have been found (Hanušovský et al, 2020).…”
Section: Proteins Peptides and Amino Acidsmentioning
confidence: 81%
“…Proteins are Table 1 Chemical Composition of grape by-products concerning Fiber, Proteins, Minerals, Vitamins, and Polyphenols (%). Sousa et al, 2014;Beres et al, 2016;Hanušovský et al, 2020 Vitamins Vitamin E 20 Vitamins are needed for normal cell function, growth, and development. Karnopp et al, 2017;Sousa et al, 2014 Vitamin C 2.6 0.5-0.01 Minerals Total minerals 1.0-6.0 0.9-6.8 0.9-5.7 1.3 3.8 0.9-7. comprised of ca.…”
Section: Proteins Peptides and Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous research has shown that the anthocyanin content of a given cultivar is not necessarily positively linked with anthocyanin concentration in the resulting wine. The lack of association was due to the partial preservation by cell-wall polymers of these anthocyanins in the skin cells [2,11,12].…”
Section: Introductionmentioning
confidence: 99%